Management and Evaluation Program PAUD University - Novrieta, Dina; Listini, Listini (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2017)
Abstract: Early childhood education is a development interface, the development of children combines the innate potential (genetic) and potential environmental influences.Thus, social skills in management practice is necessary.This can be understood because the ability to socialize and communicate with others is very decisive in achieving organizational goals.This can be understood because the ability to socialize and communicate with others is very decisive in achieving organizational goals.Implementation of early childhood that is more pressing on academic activities (reading, writing, and arithmetic) and memorization that is less meaningful for children, should be directed to learning that is centered on the interests of children by applying learning in accordance with the developmental (Developmentally Appropriate Practice) DAP. Abstrak: Pendidikan anak usia dini adalah pengembangan antarmuka, perkembangan anak yang menggabungkan potensi bawaan (genetik) dan pengaruh lingkungan potensial. Jadi, keterampilan sosial dalam praktik manajemen diperlukan. Hal ini dapat dipahami karena kemampuan bersosialisasi dan berkomunikasi dengan orang lain sangat menentukan. dalam mencapai tujuan organisasi. Hal ini dapat dipahami karena kemampuan bersosialisasi dan berkomunikasi dengan orang lain sangat menentukan dalam mencapai tujuan organisasi. Penerapan pendidikan anak usia dini yang lebih menekankan pada kegiatan akademik (membaca, menulis, dan berhitung) dan menghafal yang kurang bermakna bagi anak-anak, harus diarahkan untuk pembelajaran yang berpusat pada minat anak-anak dengan menerapkan pembelajaran sesuai dengan DAP perkembangan (Praktik Tepat Guna Pembangunan).